Efikasi Diri Menurunkan Kendala dalam Berperilaku Sehat - Koerniawan, Dheni; Sanny Frisca (Jurnal Ventilator, 2023)
Healthy behaviours are formed because individuals make decisions and commit to continuing habits that support the improvement or maintenance of health. Self-efficacy gives confidence to individuals to achieve goals to achieve good health conditions, but it is not uncommon for individuals to experience barriers in the commitment process. This study aims to determine the relationship between self-efficacy and barrier to healthy behaviour. Researchers used cross section as a research design to take parameters of 186 respondents taken randomly which then the data will be analyzed in descriptive and inferential correlations. The results showed that there was a significant moderate positive relationship between self-efficacy and obstacles to healthy behaviour. Therefore, it is recommended to provide health services that focus on increasing confidence in individuals in order to reduce the constraints felt and prescribed by individuals and can study other factors that can also reduce barriers in healthy behaviour.